Serum Progesterone Concentrations in Indigenous Nigerian Guinea Fowls - Onyeanusi, B.I. (International Journal of Poultry Science, 2007)
The serum progesterone concentrations of indigenous guinea fowls in Zaria were measured over a period of 12 months (January to December) using 480 adult female guinea fowls. The concentrations ranged between 1.04 and 3.50 ng/ml. The highest level, 3.50 ng/ml, was recorded in the month of June while the lowest level, 1.04 ng/ml was in October and December. Statistically, the serum concentrations of progesterone did not significantly (p>0.05) relate to the weights and total length of the reproductive organs. There were no uniform graphical correlations between the serum progesterone concentrations and the parameters of the reproductive organs.